Cover Picture: Sugar‐Based Polymers from d‐Xylose: Living Cascade Polymerization, Tunable Degradation, and Small Molecule Release (Angew. Chem. Int. Ed. 2/2021). Issue 2 (15th December 2020) - Rizzo, Antonio; Peterson, Gregory I.; Bhaumik, Atanu; Kang, Cheol; Choi, Tae‐Lim
Abstract : D‐xylose … . .. can be transformed into a polymerizable enyne sugar‐based monomer, as shown in the cover picture. Chalked in are the achieved properties of the various degradable polymers. The polymerization evolves a D‐xylose‐derived monomer to a full polymer chain which can be decomposed under mild acidic conditions, as explained by Tae‐Lim Choi et al. in their Research Article on page 849 . The act of drawing rough ideas on a board, a practice chemists still enjoy, and the coming to fruition of those ideas on a molecular level are represented by the 2D chalk board transition to 3D polymer.